ARTIKEL JURNAL PELAYANAN PUSAT KESEJAHTERAAN SOSIAL DALAM PENANGGULANGAN KEMISKINAN: PENANGGULANGAN KEMISKINAN - Nazrin - - (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2025)
SOCIAL WELFARE CENTER SERVICES IN POVERTY REDUCTION Abstrac: This study aims to determine the service of the social welfare center (Puskesos) inpoverty alleviation in Abeli Dalam Village, Puuwatu District, Kendari City. This type ofresearch is a qualitative descriptive study. Data collection techniques were carried out bymeans of observation, interviews, and documentation with 13 research informants. 5 peoplefrom the implementing team for the social welfare center (Puskesos), and 8 additionalinformants, 1 TKSK and 7 community members who are beneficiaries of the Puskesos servicein Abeli Dalam Village, Puuwatu District, Kendari City. The results showed that the social welfare center service (Puskesos) was located in thegovernment of Abeli Dalam Village by providing social welfare center services in programsincluding: Healthy Indonesia Card (KIS), Family Hope Program (PKH), Non Tunai FoodAssistance (BPNT), and Cash Social Assistance (BST). What Puskesos do to the poor are: 1)making changes in the form of activities, these activities are in the form of socialization. 2)assisting in solving problems, by providing quality service assistance to poorindividuals/families/households must have clear, uncomplicated, easy-to-understand andimplement procedures. These activities include; receiving complaints, checking the status ofpotential beneficiaries with data validation and verification processes, complaint handlingservices according to program needs in this case the KIS, PKH, BPNT, BST programs, andhandling referrals. With the number of recipients of KIS 700 people, PKH 77 KK, BPNT 137KK, and BST 6 KK. The number of recipients of services for the poor is 174 families from202 families. It is found in Puskesos services and the benefits of Community Health Centerservices for the community that can have a good impact on community welfare and povertyalleviation, and contribute to the fulfillment of the right to access health services, education,basic food assistance, and cash social assistance can be achieved.